The word of the teacher: Panoramic view on the study of the infertile couple. - Ascenzo Cabello, Jorge (2015)
Sixty-five million people worldwide suffer from the problem of conjugal sterility. Sterility of unknown cause in 14%, is due only to women at 36%, only the man in 22% and both in 28%. There is evidence that sterility in the world is declining. However, semen, in the last 50 years, are losing quality. Progress in the study of couples without children has been rapid in recent decades. The endoscopic study has marked a new era in this regard, to the extent that today, two sterile women, laparoscopy is one. As the years progress, more sterile undergo noting that this study will not be diagnosable but by that method elements, such as endometriosis and ratification or rectification of other causes, such as tubal patency, the relationship between the fallopian tubes and ovaries, pelvic peritoneal adhesions, small fibroids, etc. It complements very well hysterosalpingography.